3-(Substituted Aryl)-1-(benzofuran-2-yl)-2-propenones, Part 1: Synthesis and Characterization of Some Novel Chalcones - Coskun, Demet; Ahmedzade, Misir (Taylor & Francis Inc, 2008)
Synthesis and characterization of some novel chalcones by condensation of 2-acetylbenzofurane and various aromatic aldehydes is described.
Keywords: Aromatic aldehydes; benzofuranes; chalcones